2000
DOI: 10.2307/3454531
|View full text |Cite
|
Sign up to set email alerts
|

On Categorizations in Analyses of Alcohol Teratogenesis

Abstract: In biomedical scientific investigations, expositions of findings are conceptually simplest when they comprise comparisons of discrete groups of individuals or involve discrete features or characteristics of individuals. But the descriptive benefits of categorization become outweighed by their limitations in studies involving dose-response relationships, as in many teratogenic and environmental exposure studies. This article addresses a pair of categorization issues concerning the effects of prenatal alcohol ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…23 Further, the complexity of alcohol consumption over time in quantity and pattern makes it very difficult to speculate as to safe levels of alcohol consumption and this may have led authors to err on the side of caution. 4 Our finding that heavy alcohol consumption was not significantly associated with poorer behavioural outcomes was unexpected. We suggest that this finding was influenced by the small number of heavy drinkers in this cohort.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…23 Further, the complexity of alcohol consumption over time in quantity and pattern makes it very difficult to speculate as to safe levels of alcohol consumption and this may have led authors to err on the side of caution. 4 Our finding that heavy alcohol consumption was not significantly associated with poorer behavioural outcomes was unexpected. We suggest that this finding was influenced by the small number of heavy drinkers in this cohort.…”
Section: Discussionmentioning
confidence: 67%
“…3 Many researchers have noted that most empirical enquiry into the effects of alcohol exposure during pregnancy has focused on and emphasised the devastating effects of high levels of alcohol exposure, often neglecting the influence of light-moderate drinking. 4 The studies that have examined the effects of low levels of exposure to alcohol and behavioural development have failed to reach consensus, perhaps in part due to a number of methodological limitations. 5 For example, the reliability of retrospective data collected up to 17 years postpregnancy has been questioned.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, terminology for FASD-related conditions has changed drastically over the years, and thus researchers might use different terms to refer to similar samples of individuals. Although research indicates that the neuropsychologic deficits do not differ between those with and without the physical features of FAS (Mattson et al, 1998;Sampson, Streissguth, Bookstein, & Barr, 2000), future research using the same diagnostic approach and classifications would enable more reliable generalizations across studies. Furthermore, in many earlier studies, research participants were individuals with PAE but not necessarily with an FASD-related diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Of the various cognitive domains affected in PAE, many studies have shown particularly poor arithmetic abilities [Goldschmidt et al, 1996;Streissguth et al, 1994], and performance has been linked to a dose-response relationship where higher PAE relates to poorer arithmetic scores [Sampson, Streissguth et al, 2000]. Additionally, those with PAE show many conduct and behavioral difficulties [Mattson, Crocker et al, 2011].…”
Section: Introductionmentioning
confidence: 99%